Hubungan raeseptor estrogen dengan Ki-67 labeling index pada meninagioma intrakranial - Abdurrahman Mouza; Iskandar Japardi; Suzy Indharty (Fakultas Kedokteran USU, 2017)
Introduction : Meningioma occurs more in women than men with ratio 2 : 1. Mitosis of meningioma is stimulatedbyfewgrowth factorsand one of itis estrogen. Expression of estrogen receptor on meningioma showsthat clinical meningioma has characteristic more aggressive. Proliferation Index can be measured by antibody of Mind Bomb (MIB-1) binding Ki-67 antigen. Ki-67 is showed on the cells which proliferating through cells cycle.Relation between estrogen receptor and cell proliferation is interesting because it has controversy.Method : This Study used Cross Sectional method for analising relation between estrogen receptor and Ki-67 in patients have been diagnosed meningioma. This study has been done at general hospital H. Adam Malik Medan and laboratorium of patologi anatomi at Murni Teguh hospital.This study did in Oktober-November 2013.Result : In this study is almost meningioma grade I stained Ki-67 not have mitosis with amount 13 sample (43.3%) or positive mitosis is 14 sample (45%). While immunohistochemistry staining of estrogen receptor on meningioma grade I has 25 negative sample (83.3%) and 14 positive sample (51.8%). All of grade I and II are negative.Relation of these staining was used Chi-Square with limit value p<0.05. This result is p=0.677 that shows no significance relation between estrogen receptor and labeling Index Ki-67.Conclusion : These histopatology have many frequents type that is 16 cases of meningothelial meningioma (53.3%), fibroblastic meningioma, and 4 cases transitional meningioma (13.3%). The result is no relation between estrogen receptor and Ki-67 with p=0.667 (p>0.05).Other results are no relation Ki-67 with age p=0.204 (p>0.05) and sex p=0.121 (p>0.05). Keywords : estrogen receptor, Ki-67, meningioma